2001
DOI: 10.1023/a:1013311632207
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The antimicrobial properties of volatile aromatic oils from medicinal as well as other edible plants has been recognized since antiquity. Origanum oil, which is used as a food flavoring agent, possesses a broad spectrum of in vitro antimicrobial activities attributed to the high content of phenolic derivatives such as carvacrol and thymol. In the present study, antifungal properties of origanum oil were examined both in vitro and in vivo. Using Candida albicans in broth cultures and a micro dilution method, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(48 citation statements)
references
References 13 publications
1
40
0
3
Order By: Relevance
“…[33] It is active against oral bacteria associated with dental caries and periodontal disease[34] and effective against a large number of other bacteria[35363738] and virus. [39] Previous studies have reported biological activities of eugenol including antifungal,[404142] anti-carcinogenic,[43] anti-allergic,[4445] anti-mutagenic activity,[46] antioxidant[47] and insecticidal[48] properties. In our study, eugenol oil showed antimicrobial activity at the lowest concentration against all organisms compared with all essential oils such as for C. albicans with MIC, MFC: 0.1 μl/ml, for S. aureus with MIC, MBC: 0.4 μl/ml, for E. coli and for E. facelis with MIC, MBC: 1 μl/ml respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[33] It is active against oral bacteria associated with dental caries and periodontal disease[34] and effective against a large number of other bacteria[35363738] and virus. [39] Previous studies have reported biological activities of eugenol including antifungal,[404142] anti-carcinogenic,[43] anti-allergic,[4445] anti-mutagenic activity,[46] antioxidant[47] and insecticidal[48] properties. In our study, eugenol oil showed antimicrobial activity at the lowest concentration against all organisms compared with all essential oils such as for C. albicans with MIC, MFC: 0.1 μl/ml, for S. aureus with MIC, MBC: 0.4 μl/ml, for E. coli and for E. facelis with MIC, MBC: 1 μl/ml respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among the natural products, plants contain diverse components that are important sources of biologically active molecules [50, 133, 134]. In fact, the activity of plant crude extracts against different microorganisms has been reported, that is, strong antifungal activity of some major components of essential oils [135, 136]. In this regard, the antibiofilm activity of terpenes and the exceptional efficiency of carvacrol, geraniol, and thymol, in the treatment of candidiasis associated with medical devices, have been demonstrated [137].…”
Section: Need Of New Antifungal Agentsmentioning
confidence: 99%
“…Studies found that origanum oil exhibited antimicrobial activity as well as antifungal properties (Calo et al, 2015;Manohar et al, 2001). It was reported that lemon juice and vinegars showed inhibitory activities against C. perfringens spore germination and outgrowth on reduced salt (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%